2015
DOI: 10.1007/s12105-015-0663-8
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Intercalated Duct Lesion of the Parotid: Diagnostic Challenges of a Recently Described Entity with Fine Needle Aspiration Findings

Abstract: Intercalated duct lesions (IDL) of the salivary glands are recently described, and encompass both hyperplasia and benign neoplasms that remain incompletely understood. IDLs have been linked to various benign and low-grade malignant salivary gland neoplasms. We herein present a case of a 77 year old woman with an IDL of the parotid composed of both a hyperplastic and an adenomatous component and report, for the first time, the fine needle aspiration findings of such a lesion. This case illustrates the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…According to the largest study to date, describing a total of 32 IDL cases, the female to male sex ratio was 1.7:1 (19 women, 11 men, 2 unknown) and the mean age during diagnosis was 53.8 years[ 1 ]. We have found two other similar papers that report IDL cases originating from the parotid gland as hyperplastic and hybrid forms[ 9 , 10 ]. Mok et al [ 9 ] reported a hybrid form of parotid gland IDL where such lesion for the first time was detected by fine needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to the largest study to date, describing a total of 32 IDL cases, the female to male sex ratio was 1.7:1 (19 women, 11 men, 2 unknown) and the mean age during diagnosis was 53.8 years[ 1 ]. We have found two other similar papers that report IDL cases originating from the parotid gland as hyperplastic and hybrid forms[ 9 , 10 ]. Mok et al [ 9 ] reported a hybrid form of parotid gland IDL where such lesion for the first time was detected by fine needle aspiration biopsy.…”
Section: Discussionmentioning
confidence: 90%
“…We have found two other similar papers that report IDL cases originating from the parotid gland as hyperplastic and hybrid forms[ 9 , 10 ]. Mok et al [ 9 ] reported a hybrid form of parotid gland IDL where such lesion for the first time was detected by fine needle aspiration biopsy. They also forewarn potential differential diagnostic pitfalls associated with varied architectural features proposing its’ special awareness during microscopic evaluation.…”
Section: Discussionmentioning
confidence: 90%
“…Intercalated duct lesions are arbitrarily divided into IDA -if encapsulated and discretely separated from adjacent acinar units, and intercalated duct hyperplasia (IDH) -if unencapsulated and blending into the adjacent acinar units. [3][4][5] The ductal cells of IDA resemble those of non-neoplastic intercalated ducts on immunohistochemistry, staining diffusely with CK7 and S100, and focally for ER and lysozyme while CK14 and Calponin highlight the thin myoepithelial cells surrounding the ductal cells. 1,3,4 Immunohistochemical stains for myoepithelial cells were not requested as we felt that the participation of acinar cells in a characteristic manner was sufficiently diagnostic of the entity.…”
Section: Under the Microscopementioning
confidence: 99%
“…Basal cell adenocarcinoma importantly demonstrates an invasive growth pattern. 3,5 IDA on the other hand are small and infrequently seen macroscopically, most often measuring less than 5 mm in diameter. 2 Both IDA and IDL in general have an excellent prognosis upon complete surgical excision and recurrences are not reported.…”
Section: Under the Microscopementioning
confidence: 99%
“…Intercalated epithelial cells constitute a relatively minor portion of salivary gland and explains the apparent absence of PSMA in some studies [19 , [91 , 262] . The role of PSMA in the intercalated epithelia cells is not known, but interestingly these cells give rise to neoplasias just as the PSMA expressing cells in the prostate do [263 , 264] .…”
Section: Introductionmentioning
confidence: 99%